2015
DOI: 10.1039/c5ra15116c
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of acidic sites of nanoscopic hydroxylated magnesium fluorides by FTIR and 15N MAS NMR spectroscopy

Abstract: Lewis and Brønsted sites were quantified in a series of weak acidic hydroxylated magnesium fluorides by Furthermore, it is shown that the transfer of molar extinction coefficients from one catalyst to another may lead to wrong results. Molar extinction coefficients and concentrations of acidic sites determined by FTIR spectroscopy are affected by grinding and probably the particle size of the sample. High temperature during FTIR experiments has further impact on the quantification results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…When FTIR and the extinction coefficients cited in the literature were used to determine the Brønsted and Lewis acid site densities of SPP‐2 and MCM‐22, much lower BAS densities were obtained than those determined by Hoffman elimination of isopropylamine using the RGC technique. Other studies have shown similar discrepancies and questioned the used extinction coefficients . For this reason, we only use the FTIR data in a qualitative manner to confirm that a significant fraction of acid sites in SPP‐2 (Si/Al ratio ~60) are Lewis acid sites, and that the concentration of BASs is higher than that of Lewis acid sites.…”
Section: Resultsmentioning
confidence: 92%
“…When FTIR and the extinction coefficients cited in the literature were used to determine the Brønsted and Lewis acid site densities of SPP‐2 and MCM‐22, much lower BAS densities were obtained than those determined by Hoffman elimination of isopropylamine using the RGC technique. Other studies have shown similar discrepancies and questioned the used extinction coefficients . For this reason, we only use the FTIR data in a qualitative manner to confirm that a significant fraction of acid sites in SPP‐2 (Si/Al ratio ~60) are Lewis acid sites, and that the concentration of BASs is higher than that of Lewis acid sites.…”
Section: Resultsmentioning
confidence: 92%
“…This technique uses also probe molecules such as pyridine, phosphines or trialkylphosphine oxides, which interact with the Lewis and Brønsted sites of the solid material providing information which complements that obtained by vibrational spectroscopy. [11][12][13][14][15] ACF and HS-AlF 3 are very strong Lewis acids, equal or even stronger than SbF 5 in some cases. Well-known synthesis procedures make these materials available as heterogeneous catalysts for a large variety of reactions.…”
Section: Introductionmentioning
confidence: 97%
“…The frequency of this mode is affected by the interaction between the pair of solitary nitrogen pyridine molecules and the Ti 4+ ions at the substrate surface. The band at 1530 cm −1 identifies the formation of pyridinium ions (PyH + ) on the surface of the catalyst, associated with Brønsted acid sites. Finally, the low‐intensity band at 1490 cm −1 is due to the two contributions of both Brønsted and Lewis acid sites .…”
Section: Resultsmentioning
confidence: 99%